Double-Layered Lateral Meniscus in an 8-Year-Old Child: Report of a Rare Case - Susumu Araki; Mitsuhiko Kubo; Kosuke Kumagai; Shinji Imai (Case Reports in Orthopedics)
Reports of congenital abnormalities of the lateral meniscus include discoid meniscus, accessory meniscus, double-layered meniscus, and ring-shaped meniscus. Particularly, only a few cases of double-layered meniscus have been reported. We report a case of double-layered lateral meniscus, in which an additional semicircular meniscus was observed under the normal lateral meniscus. The accessory hemimeniscus was resected by means of arthroscopic surgery. This case demonstrates an interesting and extremely rare anatomical abnormality of the lateral meniscus.